2021
DOI: 10.1371/journal.pone.0258414
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of inappropriate prescriptions in older adults through the support of Asynchronous Geriatric Counseling Online (AGAlink): Implemented in primary care

Abstract: Background/Aim Medication prescription is a fundamental component in the care of the elderly. Several characteristics of aging and geriatric medicine affect prescriptions for these people and make the selection of drug therapy a difficult and complex process. The objective of this study is to develop a geriatric portal for asynchronous online counseling (AGAlink) for use by physicians specializing in family medicine to reduce medication problems among older adult patients in the first level of care. Method A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
0
0
1
Order By: Relevance
“…Selain konteks etika profetik, aksiologi mencakup estetika dari perspektif pedagogis, yang berkaitan dengan seni terkait nilai-nilai kreasi atau kreativitas, namun nilai estetika juga harus menjadi indikator penting dalam dunia pendidikan. dalam proses pengembangan pedagogik yaitu dengan pendekatan estetika moral (Avalos-Mejia et al, 2021). Artinya, pendidikan bertujuan untuk menciptakan atau membentuk kepribadian yang kreatif, artistik, sehingga pendidikan tetap menarik dan pembelajaran selalu berkelanjutan, terarah dan relevan (Armanto et al, 2021).…”
Section: Pandangan Aksiologi Cyber Counselingunclassified
“…Selain konteks etika profetik, aksiologi mencakup estetika dari perspektif pedagogis, yang berkaitan dengan seni terkait nilai-nilai kreasi atau kreativitas, namun nilai estetika juga harus menjadi indikator penting dalam dunia pendidikan. dalam proses pengembangan pedagogik yaitu dengan pendekatan estetika moral (Avalos-Mejia et al, 2021). Artinya, pendidikan bertujuan untuk menciptakan atau membentuk kepribadian yang kreatif, artistik, sehingga pendidikan tetap menarik dan pembelajaran selalu berkelanjutan, terarah dan relevan (Armanto et al, 2021).…”
Section: Pandangan Aksiologi Cyber Counselingunclassified
“…The US study suggested having pharmacists do medication reviews to coordinate medical records across clinical settings (17). A study done in Mexico that studied Computerized clinical decision support systems (CCDSS) found that 40% of physicians thought that it would allow them to improve their daily practice as it "solved their doubts and above all it provided them with new options to solve their prescription problems" (20).…”
Section: Introductionmentioning
confidence: 99%